A harvest of hope - Snelling, Lauraine (Snelling, Lauraine. Song of Blessing, 2015)
"In the early 1900s, Miriam Hastings leaves Chicago after burying her mother and returns to Blessing, North Dakota, to carry on her nursing studies. Despite her continued resistance, Trygve Knutson continues his pursuit of her heart"--